Diagnostic value of 3D fluid attenuated inversion recovery sequence in multiple sclerosis. (May 2015) - Gramsch, Carolin; Nensa, Felix; Kastrup, Oliver; Maderwald, Stefan; Deuschl, Cornelius; Ringelstein, Adrian; Schelhorn, Juliane; Forsting, Michael; Schlamann, Marc
Background: Magnetic resonance imaging (MRI) is an indispensable tool in the diagnostic work-up of multiple sclerosis (MS). To date, guidelines suggest MRI protocols containing axial dual-echo, unenhanced and post-contrast T1-weighted sequences. Especially the usage of dual-echo sequences has markedly improved the ability of MRI to detect cortical and infratentorial lesions. Newer 3D FLAIR sequences are supposed to provide even more positive imaging features such as improved detection of white matter lesions and a better resolution due to smaller slice thickness. Purpose: To evaluate the diagnostic impact of 3D FLAIR sequences in comparison to conventional T2 and PD sequences. Material and Methods: Examinations of 20 MS patients (10 women, 10 men) were reviewed retrospectively. All patients received MRI standard protocol containing PD and T2 sequences and a mid-sagittal T2 sequence. Additionally an isotropic 3D FLAIR sequence was performed. Whole-brain lesion load and number of lesions in juxtacortical, infratentorial, and midcallosal localizations were assessed by two observers independently and compared. Results: Whole lesion load and the count of detectable lesions at the 3D FLAIR sequence were significantly higher in the juxtacortical and infratentorial regions compared to the PD/T2 sequence. Detection rate of midcallosal lesions did not differ significantly in sagittal T2 and 3D FLAIR sequence. Conclusion: 3D FLAIR sequences can improve the detection of brain lesions in patients with MS and are even more sensitive in depicting lesions in cortical and infratentorial locations than current dual-echo sequences. The sequence can replace both PD/T2 sequences and mid-sagittal T2 sequences of the corpus callosum.